2022
DOI: 10.3389/fpsyg.2022.775679
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Mindfulness, and Job Burnout of Social Workers in China

Abstract: In the last 20 years, amid extensive social and economic reforms, China’s social structure and community life have changed considerably. A large number of social workers are needed to provide many more social services to community residents. The central government has issued many policies to rapidly develop human service organizations and increase the number of social workers. Thus, by the end of 2019, the number of social workers has reached more than 1.5 million in China. At the same time, local governments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 69 publications
1
12
0
2
Order By: Relevance
“…The core idea of TM involves having the self-awareness to truly experience the present moment consciously and non-judgmentally. Individuals with higher levels of TM are more focused on the awareness and self-acceptance of their physical and mental feelings, thereby reducing the risks of mental rumination and emotional dysregulation and enhancing their perceptions of social support ( 4 ), which results in an effective increase of WB in their minds ( 76 ). The occurrence of burnout can be prevented through the influence of various mediating effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The core idea of TM involves having the self-awareness to truly experience the present moment consciously and non-judgmentally. Individuals with higher levels of TM are more focused on the awareness and self-acceptance of their physical and mental feelings, thereby reducing the risks of mental rumination and emotional dysregulation and enhancing their perceptions of social support ( 4 ), which results in an effective increase of WB in their minds ( 76 ). The occurrence of burnout can be prevented through the influence of various mediating effects.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid developments in the social work sector in China have attracted increasing social attention to the problem of burnout. Consequently, scholars have attempted to examine the factors related to burnout among SWs, and one of the factors is social support ( 4 ). Some studies have suggested that the effective work performance levels among Chinese SWs depend on the support they receive from their family, friends, team members, and especially, leaders.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…First, according to conservation of resources theory, employees will try to minimize their perceived resource loss by reducing efforts and avoiding work. When employees experience psychological contract breach continuously, their psychological resources become excessively consumed or even exhausted (Xie et al, 2022), which will eventually manifest as job burnout. At the same time, the continuous interruption of psychological resources will increase employees' frustration at work, which will cause job stress and indirectly lead to job burnout (Wu et al, 2021).…”
Section: The Mediating Role Of Job Burnoutmentioning
confidence: 99%
“…First, according to the theory of emotional events, employees' work attitudes and behavior will be affected by their emotional experiences. As a negative emotional experience, job burnout naturally reduces employee satisfaction (Xie et al, 2022). New generation of employees have unique personalities and psychological characteristics, and rich and diverse job demands (Cafer et al, 2021).…”
Section: The Mediating Role Of Job Burnoutmentioning
confidence: 99%